Efficiency and catch dynamics of collapsible square and conical crab pots used in the red king crab (Paralithodes camtschaticus) fishery - Stiansen, Stian; Fernø, Anders; Furevik, Dag; Jørgensen, Terje; Løkkeborg, Svein (2016)
-